Fältskiktsarter i naturlika planteringar - Jerleke, Anna (2009)
This paper appeals to professionals working with green questions. It intends to create a discussion about which plant species that can be established in a fieldlayer of a naturelike planting on fertile agricultural land. To initiate the essay, a studie of which values that can be connected with an establishment of a fieldlayer was performed . A part of Tor Nitzelius Park in Alnarp, a so called naturlike planting on fertile agricultural land, was used as a model for the choice of species. With the aid of soil values, photos and a list of current species, interviews with four ecologists were performed. The choice of species and comments made during the interviews were compiled. The species were analyzed through Ellenbergs indicator values. Even though the biotope is planted, the ecologists had no difficulty in selecting species and there were several species that more than one ecologist choose. I analyzed the species which had been selected and concluded that a plant that would thrive in this environment should be able to cope with: shade, moderate cold, an oceanic environment, and also a mild and humid climate. Furthermore, the plant would have to be able to thrive in soil that is slightly alkaline. The plant would also have to be permissive to nitrogen. The comments the ecologists made during the interviews deals with factors that may affect the establishment of plants and enable a richness of species.